Expression of smooth muscle-specific alpha-isoactin in cultured vascular smooth muscle cells: relationship between growth and cytodifferentiation (The Rockefeller University Press, 1986)
The relationship between growth and cytodifferentiation was studied in cultured rat aortic smooth muscle cells (SMCs) using expression of the smooth muscle (SM)-specific isoactins (Vanderkerckhove, J., and K. Weber, 1979, Differentiation, 14:123-133) as a marker for differentiation in these cells. Isoactin expression was evaluated by: (a) measurements of fractional isoactin content and synthesis ([35S]methionine incorporation) by densitometric evaluation of two- dimensional isoelectric focusing sodium dodecyl sulfate gels, and (b) immunocytological examination using SM-specific isoactin antibodies. Results showed the following: (a) Loss of alpha-SM isoactin was not a prerequisite for initiation of cellular proliferation in primary cultures of rat aortic SMCs. (b) alpha-SM isoactin synthesis and content were low in subconfluent log phase growth cells but increased nearly threefold in density-arrested postconfluent cells. Conversely, beta-nonmuscle actin synthesis and content were higher in rapidly dividing subconfluent cultures than in quiescent postconfluent cultures. These changes were observed in primary and subpassaged cultures. (c) alpha-SM actin synthesis was increased by growth arrest of sparse cultures in serum-free medium (SFM; Libby, P., and K. V. O'Brien, 1983, J. Cell. Physiol., 115:217-223) but reached levels equivalent to density-arrested cells only after extended periods in SFM (i.e., greater than 5 d). (d) SFM did not further augment alpha-SM actin synthesis in postconfluent SMC cultures. (e) Serum stimulation of cells that had been growth-arrested in SFM resulted in a dramatic decrease in alpha-SM actin synthesis that preceded the onset of cellular proliferation. These findings demonstrate that cultured vascular SMCs undergo differential expression of isoactins in relation to their growth state and indicate that growth arrest promotes cytodifferentiation in these cells.